Theatre and feeling - Hurley, Erin, 1969- (Theatre&, 2010)
"This book explores the idea that, for many people, theatre is a passion. It provides an intellectual framework for the range of emotional experience engendered by the theatre, bringing the issue of theatrical feeling into focus as both a research object and a method in theatre studies"--